An Approach to Measuring Impact and Effectiveness of Educational Science Exhibits - Mark Tucker; Jon Bricker; Alexandria Huerta (Journal of Applied Communications, 2011)
Exhibits are among the oldest educational media still in wide use today, and they continue to serve a particularly important role in a range of Extension and nonformal science communication settings. While agricultural and applied communicators have an established tradition of evaluating various information channels and media, there is very little published work in the discipline that describes procedures for measuring the performance or impact of educational exhibits. Evaluation is often complicated by the placement of educational exhibits in unique venues such as fairs and shopping malls that may not lend themselves to conventional research procedures or learning metrics associated with formal education settings. This professional development paper draws from the free-choice learning literature to describe some of the special challenges that can arise in the evaluation of educational exhibits. The authors then introduce an evaluation strategy used successfully in measuring the impact and effectiveness of multiple educational exhibits over a four-year span. Developed largely from the museum-studies literature and replicated through evaluations with several exhibits, the mixed-methods strategy described here can be tailored to meet applied communicators’ specialized evaluation needs and resources. Following a discussion of this approach, the authors draw on their collective experience in sharing 10 practical steps to help frame the essential phases of a successful exhibit evaluation process.
Keywords: Exhibits; agricultural; ree-choice; educational; information; communications technology